Design and testing of electromechanical actuator for aerospace applications - Papini, Luca; Connor, Peter H.; Patel, C.; Empringham, Lee; Gerada, C.; Wheeler, Patrick (2018)
Electromechanical actuators are gaining interest in the aerospace industry within the More Electrical Aircraft (MEA) architecture. The end-goal of fully electric aircraft includes Electromechanical actuation for flight control systems. The design and testing of a flight control system for helicopter swashplate is presented in this work. The mechanical system is driven by electrical machines and controlled by dedicated power electronics, both of which fit challenging space requirements and environmental conditions. The predicted performances are validated by experimental testing of prototypes.